Degradable polyisoprene by radical ring-opening polymerization and application to polymer prodrug nanoparticles. Issue 12 (6th March 2023) - Lages, Maëlle; Pesenti, Théo; Zhu, Chen; Le, Dao; Mougin, Julie; Guillaneuf, Yohann; Nicolas, Julien
Abstract : Radical ring-opening copolymerization of isoprene and dibenzo[ c, e ]oxepane-5-thione via free-radical and controlled radical polymerizations led to degradable polyisoprene under basic, oxidative and physiological conditions with application to prodrug nanoparticles. Abstract : Radical ring-opening polymerization (rROP) has received renewed attention to incorporate cleavable linkages into the backbones of vinyl polymers, especially from cyclic ketene acetals (CKAs). Among the monomers that hardly copolymerize with CKAs are (1, 3)-dienes such as isoprene (I). This is unfortunate since synthetic polyisoprene (PI) and its derivatives are the materials of choice for many applications, in particular as elastomers in the automotive, sport, footwear, and medical industries, but also in nanomedicine. Thionolactones have been recently proposed as a new class of rROP-compatible monomers for insertion of thioester units in the main chain. Herein, we report the synthesis of degradable PI by rROP via the copolymerization of I and dibenzo[ c, e ]oxepane-5-thione (DOT). Free-radical polymerization as well as two reversible deactivation radical polymerization techniques were successfully used for the synthesis of (well-defined) P(I- co -DOT) copolymers with adjustable molecular weights and DOT contents (2.7–9.7 mol%). Reactivity ratios of r DOT = 4.29 and r I = 0.14 were determined, suggesting preferential incorporation of DOT in comparison to I. The resulting P(I- co -DOT) copolymers were successfully degraded (from −47% to −84% decrease in M n ) under basic conditions. As a proof of concept, the P(I- co -DOT) copolymers were formulated into stable and narrowly dispersed nanoparticles, showing similar cytocompatibility on J774.A1 and HUVEC cells compared to their PI counterparts. Furthermore, Gem-P(I- co -DOT) prodrug nanoparticles were synthesized by the "drug-initiated" method and exhibited significant cytotoxicity on A549 cancer cells. P(I- co -DOT) and Gem-P(I- co -DOT) nanoparticles were degraded under basic/oxidative conditions by bleach and under physiological conditions in the presence of cysteine or glutathione.